Visualizing Influenza A Virus vRNA Replication - Chiu, Ya-Fang; Huang, Yi-Wen; Chen, Chi-Yuan; Chen, Yu-Chia; Gong, Yu-Nong; Kuo, Rei-Lin; Huang, Chung-Guei; Shih, Shin-Ru (Frontiers in Microbiology, 2022)
Influenza A virus (IAV) has caused recurrent epidemics and severe pandemics. Understanding IAV replication dynamics in host cells can facilitate the development of novel antiviral strategies. In this study, we adapted an MS2-MCP live-cell imaging system to visualize IAV replication. A reporter plasmid, pHH-PB2-vMSL, was constructed by replacing part of the PB2-coding sequence in pHH-PB2 with a sequence encoding 24 copies of a stem-loop structure from bacteriophage MS2 (MSL). Binding of MS2 coat protein (MCP) fused to green fluorescent protein (GFP) enabled the detection of vRNA as fluorescent punctate signals in live-cell imaging. The introduction of pHH-PB2-vMSL into A549 cells, transduced to express an MCP-GFP fusion protein, subsequently allowed tracking of the distribution and replication of PB2-vMSL vRNA after IAV PR8 infection. Spatial and temporal measurements revealed exponential increases in vRNA punctate signal intensity, which was only observed after membrane blebbing and chromatin condensation in apoptotic cells. Similar signal intensity increases in apoptotic cells was also observed after MDCK cells, transduced to express MCP-GFP, were infected with IAV virions carrying PB2-vMSL vRNA. Notably, PB2-vMSL vRNA replication was observed to occur only in apoptotic cells, at a consistent time after apoptosis initiation. There was a lack of observable PB2-vMSL vRNA replication in non-apoptotic cells, and vRNA replication was suppressed in the presence of apoptosis inhibitors. These findings point to an important role for apoptosis in IAV vRNA replication. The utility of the MS2-imaging system for visualizing time-sensitive processes such as viral replication in live host cells is also demonstrated in this study.